2015
DOI: 10.1681/asn.2014030233
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Fibroblast Growth Factor-Inducible 14 (Fn14) Preserves the Filtration Barrier and Ameliorates Lupus Nephritis

Abstract: TNF ligand superfamily member 12, also known as TNF-related weak inducer of apoptosis (TWEAK), acts through its receptor, fibroblast growth factor-inducible 14 (Fn14), to mediate several key pathologic processes involved in tissue injury relating to lupus nephritis. To explore the potential for renal protection in lupus nephritis by targeting this pathway, we introduced the Fn14 null allele into the MRL-lpr/lpr lupus mouse strain. At 26-38 weeks of age, female Fn14-knockout MRL-lpr/lpr mice had significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 60 publications
4
116
0
Order By: Relevance
“…As a novel member of the tumor necrosis factor (TNF)-ligand superfamily, TNF-like weak inducer of apoptosis (TWEAK) promotes the expression of proinflammatory mediators from various cell types, including endothelial cells, epithelial cells, and keratinocytes (Chen et al, 2011a;Xia et al, 2014;Jin et al, 2004). Fibroblast growth factor inducible 14 (Fn14) is a sole known receptor for TWEAK, and induces the phosphorylation of IκB kinase in keratinocytes when bound to TWEAK, followed by augmented production of RANTES (regulated on activation normal T-cell expressed and secreted) (Jin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As a novel member of the tumor necrosis factor (TNF)-ligand superfamily, TNF-like weak inducer of apoptosis (TWEAK) promotes the expression of proinflammatory mediators from various cell types, including endothelial cells, epithelial cells, and keratinocytes (Chen et al, 2011a;Xia et al, 2014;Jin et al, 2004). Fibroblast growth factor inducible 14 (Fn14) is a sole known receptor for TWEAK, and induces the phosphorylation of IκB kinase in keratinocytes when bound to TWEAK, followed by augmented production of RANTES (regulated on activation normal T-cell expressed and secreted) (Jin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The current update is focused on the contribution of TWEAK/Fn14 to AKI and will not discuss the involvement of TWEAK in immune and nonimmune proteinuric kidney diseases. [6][7][8][9][10][11] TWEAK, Fn14, And CD163 TWEAK activates the Fn14 receptor and is scavenged by macrophage-derived CD163 (Fig. 1).…”
mentioning
confidence: 99%
“…Fn14-knockout MRL-lpr/lpr mice demonstrated markedly lower levels of proteinuria compared with wild-type MRL-lpr/lpr mice. Fn14-knockout mice also showed significantly attenuated glomerular and tubulointerstitial inflammation [14]. It was reported that TWEAK induced mesangial cells, podocytes, and endothelial cells to secrete pro-inflammatory chemokines including MCP-1, IP-10 and RANTES (CCL5), which are crucial in the pathogenesis of LN [15].…”
Section: Is Urinary Tumor Necrosis Factor-like Weak Inducer Of Apoptomentioning
confidence: 98%